Analysis of Determinants of MSMEs Performance - Rr. Lulus Prapti Nugroho Setiasih Surjanti; Edy Mulyantomo; Dian Triyani (International Journal of Economics Development Research (IJEDR), 2024)
Various business sectors carried out by MSMEs actors continue to experience growth and development. This fact confirms that MSMEs has promising potential for expansion and provides good opportunities for business actors. The same goes for MSMEsactors in Bendungan Village, Gajahmungkur Sub-district, Semarang. They must consistently improve their performance to continue to provide positive contributions to the local population. Social capital and financial capital need attention, besides continuously honing the human resource capabilities of MSMEs actors. Based on the above, research conducted on 103 UMKM actors in Mranggen District, Demak Regency, successfully proves that (1) partially, social capital and financial capital have a significant positive effect on MSMEs performance, and (2) human resource competence proves to strengthen the influence of social capital and financial capital on MSMEs performance. The resulting coefficient of determination is 30.3%.